Got Milk? A Proposed Model Lactation Policy for American Carceral Settings - Katherine Vega (Washington University Journal of Law & Policy, 2021)
In recent years, movements led by physicians, the government, and parents have attempted to lessen the stigma of public lactation. As a result, the popularity and publicity of breastfeeding has soared. However, the same response has not been seen within American detention centers. Vega considers the discrepancies and proposes a model policy to ensure that lactating parents be allowed to pump or breastfeed while incarcerated. This Note examines the history of this issue, lessons learned from current problems with the state of lactation in detention centers, and offers a model of a policy that treats lactation as a medical condition and right that is worthy of accommodations and protection in jails and prisons. Vega proposes broad, pro-lactation legislation that does not limit the places people can express breast milk and specifically targets carceral settings as an area of protection to ensure that these protections are granted to people who are incarcerated.
Keywords: pump; pumping; breastfeed; breastfeeding; lactate; lactation; pro-lactation; carceral; carceral setting; detention; detention setting; jail; jails; prison; prisons; incarcerated; incarcerate; medical condition; accommodation; accommodations; protection; protections